Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.3389/fmicb.2014.00245
|View full text |Cite
|
Sign up to set email alerts
|

Identification of genes specifically required for the anaerobic metabolism of benzene in Geobacter metallireducens

Abstract: Although the biochemical pathways for the anaerobic degradation of many of the hydrocarbon constituents in petroleum reservoirs have been elucidated, the mechanisms for anaerobic activation of benzene, a very stable molecule, are not known. Previous studies have demonstrated that Geobacter metallireducens can anaerobically oxidize benzene to carbon dioxide with Fe(III) as the sole electron acceptor and that phenol is an intermediate in benzene oxidation. In an attempt to identify enzymes that might be involved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 50 publications
(64 reference statements)
1
12
0
Order By: Relevance
“…In contrast to many aerobic benzene-degrading pure cultures, only few anaerobic benzene-degrading axenic cultures have been described. The hyperthermophilic archaeon Ferroglobus placidus was proposed to employ a putative UbiD-related carboxylase in anaerobic benzene activation 17 , and anaerobic benzene oxidation in Geobacter metallireducens was shown to proceed via hydroxylation to phenol 18 , 19 . In contrast to these strictly anaerobic iron-reducers that employ oxygen-independent activation routes, the chlorate-reducing Alicycliphilus denitrificans strain BC 20 was shown to degrade benzene via an oxygenase-mediated pathway 21 .…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to many aerobic benzene-degrading pure cultures, only few anaerobic benzene-degrading axenic cultures have been described. The hyperthermophilic archaeon Ferroglobus placidus was proposed to employ a putative UbiD-related carboxylase in anaerobic benzene activation 17 , and anaerobic benzene oxidation in Geobacter metallireducens was shown to proceed via hydroxylation to phenol 18 , 19 . In contrast to these strictly anaerobic iron-reducers that employ oxygen-independent activation routes, the chlorate-reducing Alicycliphilus denitrificans strain BC 20 was shown to degrade benzene via an oxygenase-mediated pathway 21 .…”
Section: Introductionmentioning
confidence: 99%
“…Some years later, anaerobic benzene oxidation by Geobacter was successfully proven (Zhang et al ., ). And even the genes for anaerobic benzene oxidation were identified for Geobacter metallireducens (Zhang et al ., ). Thus, it was not surprising that one of the first MET experiences on aromatics removal evaluated the ability of Geobacter metallireducens to oxidize toluene, benzene or naphthalene to carbon dioxide using a graphite electrode as electron sink (Zhang et al ., ).…”
Section: Organic Contaminantsmentioning
confidence: 97%
“…Assessment of ethylbenzene, xylene, and naphthalene degradation can also occur via metabolite analysis. For benzene, a compound‐specific metabolite has been identified for aerobic conditions (Gibson and Parales ), but the few identified anaerobic metabolites produced from benzene, that is, benzoic acid and phenol (Abu Laban et al ; Zhang et al ; Zhang et al ), can have many sources and therefore, are considered ambiguous biomarkers. As such, detection of benzoic acid and phenol by itself is not sufficient to demonstrate anaerobic benzene biodegradation.…”
Section: Diagnostic Toolsmentioning
confidence: 99%
“…It is important to note that the information in Table is evolving because ongoing research continues to reveal new findings on how microorganisms metabolize contaminants. For example (Zhang et al ; Zhang et al ) have recently confirmed that phenol is an early metabolite during anaerobic benzene biodegradation, whereas Dong et al () recently identified benzoyl‐CoA as a metabolite of anaerobic benzene degradation.…”
Section: Diagnostic Toolsmentioning
confidence: 99%